Brain tissue strains vary with head impact location: A possible explanation for increased concussion risk in struck versus striking football players. (April 2019) - Elkin, Benjamin S.; Gabler, Lee F.; Panzer, Matthew B.; Siegmund, Gunter P.
Abstract: Background: On-field football helmet impacts over a large range of severities have caused concussions in some players but not in other players. One possible explanation for this variability is the struck player's helmet impact location. Methods: We examined the effect of impact location on regional brain tissue strain when input energy was held constant. Laboratory impacts were performed at 12 locations distributed over the helmet and the resulting head kinematics were simulated in two finite element models of the brain: the Simulated Injury Monitor and the Global Human Body Model Consortium brain model. Findings: Peak kinematics, injury metrics and brain strain varied significantly with impact location. Differences in impact location explained 33 to 37% of the total variance in brain strain for the whole brain and cerebrum, considerably more than the variance explained by impact location for the peak resultant head kinematics (8 to 23%) and slightly more than half of the variance explained by the difference in closing speed (57 to 61%). Both finite element models generated similar strain results, with minor variations for impacts that generated multi-axial rotations, larger variations in brainstem strains for some impact locations and a small bias for the cerebellum. Interpretation: Based on this experimental and computational simulation study, impact location on the football helmet has a large effect on regional brain tissue strain. We also found that the lowest strains consistently occurred in impacts to the crown and forehead, helmet locations commonly associated with the striking player.